Influence of the coefficient of non-uniformity of expansion of clay soil specimen on mechanical characteristics - A. Z. Ter-Martirosyan; G. O. Angelo; L. Yu. Ermoshina; I. A. Bokov (Vestnik MGSU)
Introduction. Determination of strength and deformation characteristics of soils composing the soil mass is the key process of calculation and design of structures of all types. High accuracy in determining mechanical characteristics plays a huge role at every stage of project development. Triaxial compression units are one of the most popular and widely used devices for laboratory research, as this type of testing allows you to reproduce the stress-strain state of the soil mass and determine its mechanical characteristics most accurately.Materials and methods. Experimental studies were performed on clay soil specimens (sandy loam, loam, clay) in a triaxial compression device in a consolidated-drained mode in order to study the effect of the coefficient of non-uniformity of expansion of the soil specimen on its mechanical properties.Results. Analyzing the data of experimental studies, it was found that the coefficient of non-uniformity of expansion of specimen b has a significant effect on the obtained values of the mechanical characteristics of clay soil, namely: the values of the angle of internal friction in the medium increased by 5 %; the values of specific adhesion increased by 4.4 % on average. However, it should be noted that despite the increase in the strength characteristics of the tested soil specimens, the exclusion of the coefficient b from the treatment process led to a decrease in the values of the secant deformation modulus at 50 % strength E50 by an average of 4.5 %.Conclusions. The obtained overestimated values of strength characteristics φ, c and underestimated values of deformation characteristics E50 are not critical, however, to increase the accuracy of calculations performed based on the results obtained as a result of in-house processing of laboratory test specimens, the coefficient of uneven expansion b of the specimen should be taken into account.